KEPEMIMPINAN PEREMPUAN DI DESA WIAU LAPI KECAMATAN TARERAN KABUPATEN MINAHASA SELATAN - RUMIMPUNU, SOFANY RUSSO; RARES, JOYCE JACINTA; TAMPI, GUSTAF BUDI (Sam Ratulangi University, 2018)
Abstrack Leadership is a thing that should be owned by every leader of the organization. Aleader must be able to respond to changes that occur and lead their organizations. Women's leadershiphas always been a matter of interest to interest, especially with so many theories that clarify about theleadership of women. This is certainly not in spite of the complexity of the problems relating to womenthemselves. An overview of women's Leadership can be seen in the village of Tareran Sub-district WiauLapi South Minahasa Regency. Research methods used in this research is descriptive qualitativeresearch methods. The results of this research show that the woman had already been given the freedomto lead, but in some ways still felt lacking and could be a big problem, as the communication should stillbe increased because of the still existing of taste confidence from the community or Councilor to conveyan idea also input, further establishing communication with the opposite sex. In motivating this is morevisible to the village to the community are valued less. For referrals work, felt good already but stillneeds to be improved especially when communicating with the opposite sex. In innovation is still veryless because of big changes have not provided for the village. Then raise the degree in women wherestill has not appeared in the village see still lack women to want to appear although weaker with the oldlaw now is women can represent. In the old law still troubleshooting using the feelings so that anyproblems can be resolved only with deliberation. Based on the results of the above conclusions, theresearchers advise that women should maintain leadership values that either one of them buildcommunication without limits, more motivating ourselves, referral work is always based on rules,multiply the innovation that can build the village and help the community, provide training andsocialization are more specific and unequivocal stance regarding women and fair very expected that insolving and decision-making is done in a balanced way.Keywords: Leadership, Women, Participative, Democratis.